DEVELOPMENT STRATEGY FOR RELIGIOUS TOURISM OBJECTS DUMAI ISLAMIC CENTER IN DUMAI CITY - Irmawati; As'ari, Hasim (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aimed to design appropriate strategies for the development of the Dumai Islamic Center religious tourism object in Dumai City through a SWOT analysis method. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results show that, based on the SWOT analysis, the most suitable strategy for developing the Dumai Islamic Center religious tourism object is an aggressive strategy. This strategy is implemented by utilizing technological and informational advancements to optimize the promotion of the Dumai Islamic Center as a religious tourism icon, enhancing religious events to a national or international scale to attract visitors from various regions, and taking advantage of its strategic location to develop micro, small, and medium enterprises, as well as encouraging entrepreneurs to produce and provide Dumai’s signature souvenirs and culinary products. Furthermore, routine annual activities and government support are utilized to create employment opportunities in the tourism sector.